1994
DOI: 10.1007/bf00967320
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characteristics of primary and passaged cultures of primate brain microvessel endothelial cells

Abstract: Rhesus macaque monkey brain microvessel endothelial cells (BMECs) were isolated and grown in culture in an effort to establish an appropriate primate in vitro model of the endothelial component of the blood-brain barrier. The presence of Factor VIII antigen, alkaline phosphatase, gamma-glutamyl transpeptidase, lactate dehydrogenase, total protein, and the passive permeability properties was documented for both primary and passaged cultures. Primate BMECs were shown to exhibit similar morphological and biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Indeed, many authors have reported the existence of BBB in many vertebrates (Abbott 2005). Several studies demonstrated the presence of AP activity in capillary endothelium of rat brain (Meunier and Bouchaud 1978;Liu et al 1979;Inomata et al 1984), mouse brain (Vorbrodt et al 1981(Vorbrodt et al , 1986, goat brain (Vorbrodt and Trowbridge 1991), avian species (Stewart and Wiley 1981), frog brain (Latker et al 1987;Lazzari et al 1989), cat brain (Vorbrodt et al 1985), primate brain (Shi and Audus 1994), bovine brain (Brunel et al 1969). Recently, the impermeability of cerebral microvessels has been first reported in zebrafish following in vivo experimentation of permeability assays (sulfo-NHS-biotin and horseradish peroxydase) and immunoreactivity towards integral proteins (Claudin-5 and Zonula Occludens-1) of the tight junctions (Jeong et al 2008).…”
Section: Species Specificitymentioning
confidence: 95%
“…Indeed, many authors have reported the existence of BBB in many vertebrates (Abbott 2005). Several studies demonstrated the presence of AP activity in capillary endothelium of rat brain (Meunier and Bouchaud 1978;Liu et al 1979;Inomata et al 1984), mouse brain (Vorbrodt et al 1981(Vorbrodt et al , 1986, goat brain (Vorbrodt and Trowbridge 1991), avian species (Stewart and Wiley 1981), frog brain (Latker et al 1987;Lazzari et al 1989), cat brain (Vorbrodt et al 1985), primate brain (Shi and Audus 1994), bovine brain (Brunel et al 1969). Recently, the impermeability of cerebral microvessels has been first reported in zebrafish following in vivo experimentation of permeability assays (sulfo-NHS-biotin and horseradish peroxydase) and immunoreactivity towards integral proteins (Claudin-5 and Zonula Occludens-1) of the tight junctions (Jeong et al 2008).…”
Section: Species Specificitymentioning
confidence: 95%
“…The effects of cell passaging on endothelin-1 and prostaglandin F2a production of bovine luteal endothelial cells (Acosta et al 2007) and on the responsiveness of bovine aortic endothelial cells to orbital shear stress (Kudo et al 2005) were also evaluated. It has been reported that in vitro passaging causes the changes in enzyme activities and total protein in primate brain microvessel endothelial cells (Shi and Audus 1994) and in LDL uptake and expression of eNOS, MCP-1, von Willebrand factor (vWF), VCAM-1, ICAM-1, and E-selectin in primate femoral artery endothelial cells with or without cytokine stimulation (Shi et al 2004). Expression of thymosin b-10 in human dermal endothelial cells (Vasile et al 2001) or specific angiotensin II receptors (AT1 and AT2) in human glomerular endothelial cells (Cresci et al 2003) was significantly influenced by in vitro passaging.…”
Section: Introductionmentioning
confidence: 99%
“…Magnification 300 ase (g-GT) has been observed upon in vitro cultivation (Meyer et al 1990). In other in vitro model systems of the blood brain barrier, the ALP activity was reported to be not entirely absent, but reduced in comparison to in vivo conditions and decreasing with increasing passage number (Vorbrodt and Trowbridge 1991;Shi and Audus 1994). When, on the other hand, cell differentiation into capillary-like sprouts was induced in immortilized brain endothelial cells by b-FGF, these sprouts resumed expression of ALP (Roux et al 1994).…”
Section: Discussionmentioning
confidence: 96%